Analysis of Morbidity Profile of Neonates Admitted in Special New-born Care Units of Gujarat - Monark Vyas; Harsh Shah (Indian Association of Preventive and Social Medicine, 2020)
Introduction: Facility Based Newborn Care (FBNC) is a critical intervention to improve child survival & to reduce neonatal mortality rate Neonatal Mortality Rate (NMR) is major challenge.Objectives: Toanalyze morbidity profile of neonates admitted in special newborn care units of a tertiary level hospitals and medical college attached hospitals of Gujarat State. Method: A cross sectional descriptive study where record based secondary data collected & analysed for key indicators from all Govt. supported Sick Newborn Care Unit (SNCUs) which are in Medical college attached hospitals, district hospitals and grant in aid trust hospitals. April 2014 to March 2016 was the study period. Results: The study found near proportions of (53%) inborn, (47%) out born admission and 44% admission of female. Out of 69,662 admissions, 67% were discharged, 16% died, 10% leaving against medical advice, and 7% referred to higher centers. Major reasons for admission were respiratory distress syndrome (RDS) (22%) and infection (21%). Conclusion: Strengthening of appropriate facility care is essential to address neonatal mortality. The health interventions needed to tackle NMR differ from those needed for infant mortality rate and under-five mortality rate.